(untitled) (Journal of Economics and Management Research, 2022)
ملخص: هدفت الدراسة الحالية إلى التعرف على واقع السمعة التنظيمية لمصرف الرافدين /فرع تكريت وبغية تحقيق هدف الدراسة فقد اعتمدت الدراسة على المنهج الوصفي التحليلي وتم اعتماد الاستبانة كأداة رئيسة لجمع البيانات وتمثل مجتمع الدراسة بـزبائن مصرف الرافدين. وتوصلت الدراسة إلى تمتع المصرف بسمعة تنظيمية جيدة. بالإضافة إلى أن المصرف لديه اهتمام عالي ببعد جودة الخدمات أكثر من باقي الأبعاد. The current study aimed to identify the reality of the organizational reputation of Rafidain Bank/Tikrit branch and in order to achieve the goal of the study, the study relied on the analytical descriptive approach and the questionnaire was adopted as a key tool for data collection and represents the study community with the customers of Rafidain Bank.The study found that the bank had a good organizational reputation. In addition, the bank has a higher interest in the quality of services than the rest of the dimensions.